Implementing sub steps in a parallel automata cellular model - Tissera, Pablo Cristian (2011)
Computer simulations using Cellular Automata (CA) have been applied with considerable success in different scientific areas. In this work we use CA in order to specify and implement a simulation model that allows to investigate behavioural dynamics for pedestrians in an emergency evacuation. A CA model is discrete and handled by rules. However several aspects of the crown behaviour should appear as a continuous phenomenon. In this paper we implement the sub steps technique in order to solve an unexpected phenomenon: the formation of holes (empty cells) both around the exit and mixed in the crowd evacuation. The holes occur when individuals of consecutive cells want move towards an exit. Additionally, the methodology allowed us to include, as a new parameter of the model, speeds associated to the pedestrians. Due to the incorporation of new features, the model complexity increases. We apply a parallel technique in order to accelerate the simulation and take advantage of modern computer architectures. We test our approaches to several environment configurations achieving important reduction of simulation time and the total evacuation time.